Pregnancy Effect on Echocardiographic Parameters in Great Dane Bitches - Melandri, Monica (Animals (Basel), 2020)
SIMPLE SUMMARY: In women, as well as in bitches, pregnancy is associated with the adaptation of the left ventricular function. Pregnancy mainly represents a status of increased volume load of the maternal heart driven by the need to supply an adequate blood flow through an augmented uterine perfusion to the developing fetuses. Consequently, cardiac morpho-functional changes are expected. Cardiac morphology and function in pregnant bitches that would develop complications may differ from those with a normal outcome. Thus, the assessment of the maternal cardiovascular function may be a useful screening tool to detect pregnancy complications in dogs. Few studies investigated the cardiac maternal adaptation in different gestational ages in dogs. Breed is a known source of variation in echocardiographic values; hence, the cardiac performance during pregnancy may also be prone to a breed-related variation. For these purposes, due to possible breed-related variations in cardiac parameters and function, and to the specific predisposition for myocardial diseases, echocardiographic changes along pregnancy in healthy Great Dane bitches were evaluated. A significant effect of the age of gestation on the increase of functional and diastolic parameters and on the decrease of systolic parameters was reported. ABSTRACT: Pregnancy is associated with adaptation of the left ventricular (LV) function. Due to differences between breeds in baseline echocardiographic values and specific predispositions for myocardial diseases, breed-specific echocardiographic parameters may be helpful to evaluate whether the systolic function varies during pregnancy. This study enrolled nine healthy Great Dane bitches with uncomplicated pregnancy. Echocardiographic M-mode and B-mode data were collected before ovulation and within 7 days of the predicted parturition term. Evaluated parameters were: LV dimension in diastole (LVd) and systole (LVs), end-diastolic (EDVI) and end-systolic (ESVI) volumes indexed to body surface area (BSA), end-diastolic (EDV) and end-systolic (ESV), end-point-septal-separation (EPSS), left atrium to aortic root ratio (LA/Ao), sphericity index (SI), ejection fraction (EF), fractional shortening (FS), stroke volume (SV), heart rate (HR), and cardiac output (CO). The ANOVA showed a statistical effect of the age of gestation (p < 0.01) on the increase of diastolic dimensions and functional parameters and on the decrease of systolic dimensions. The CO increase parallels the rise in SV and HR (p < 0.01). No statistical differences were observed for EPSS, LA/Ao, and SI. The changes in cardiac chambers and function are likely to reflect maternal adaptation to allow the fetal development in uncomplicated pregnancy. The present study provides specific echocardiographic values in uncomplicated pregnancy of Great Danes, showing that the systolic function is enhanced and that the increase in preload, observed during gestation, is the likely mechanism.